CORPORATE IDENTITY PROJECT FOR PROSPERITY OF TRANSPORT ORGANIZATION - Bieliková, A.; Klieštik, T. (Science and Transport Progress, 2005)
The article deals with corporate identity and its parts in a transport organization. The corporate identity is a strategically arranged idea based on the firm philosophy, firm vision and long-term business target. It must be confirmed by the firm’s behavior and its internal and external communication.